Novos peptídeos sintéticos e estudo da interação com membranas modelo: efeito de modificações no N-terminal na atividade lítica e antimicrobiana - Zanin, Luciana Puia Moro [UNESP] (2014)
Antimicrobial peptides (AMPs) are components of the innate immune system, which are present in the majority of the living organisms and whose interest is growing due to their potent antimicrobial activity against a broad range of microorganisms, coupled with their usually low toxicity to mammalian cells. In an effort to develop short antimicrobial peptides with the same structural characteristics that imparted selectivity to Polybia-MP1 (IDWKKLLDAALQIL-NH2): the relative positioning of acid and basic residues, an acid residue at the N-terminus, hydrophilicity and the broad polar face. MP1 is a potent antimicrobial, antitumoral and non-hemolytic peptide. We generated a peptide named L1A (IDGLKAIWKKVADLLKNT-NH2) and two analogs with N-terminus modifications; one acetylated (Ac-L1A) and other was extrinsic fluorescent labeled with ortho-aminobenzoic acid (Abz) in which the tryptophan was substituted by valine (Abz-L1A-W8V). We analyzed static and time-resolved fluorescence of tryptophan and ortho-aminobenzoic acid were used and showed significant blue shift when peptides are adsorbed in lipid vesicles and the fluorescence quenching by acrylamide showed that fluorophores in anionic vesicles, are less exposed to the solvent than in neutral vesicles. The lytic activity in vesicles showed from dose-response curves that the three peptides were more efficient in anionic vesicles moreover that the analogs were more efficient. These observations were compatible with the higher helical content (observed in Molecular Dynamics and Circular Dichroism) and deeper burying of the fluorophores in anionic vesicle. MD and CD data demonstrated a relationship between the stability of the helix and the absence of load on the N-terminal. L1A and Ac-L1A presented potent antimicrobial selective against Gram negative bacteria without being hemolyitic while Abz -L1A -W8V was mildly hemolytic